THE MULTI-CULTURAL EXPRESSION OF VISUAL RHETORIC IN FOOD PACKAGING - Farrah Hanani Ahmad Fauzi; Lili Eliana Mohd Radzuan; Fazlina Jaafar; Azian Mohd Zain (International Journal of Accounting, Finance and Business, 2022)
Packaging is able to play an important role in promoting racial integration inMalaysian. The cultural element design is abundantly visible and often ignored by us. A mixedmethod approach was employed through this study which is the quantitative and qualitativemethods. Visual analysis was conducted to analyse visual rhetoric towards two food packagingdesign. The survey was carried out 30 respondents as data collection. From the findings,illustration such as graphic, pattern or photography was indicated as the main design elementthat contributed towards culture expression. Finally, it can be concluded that majority of therespondents prefer social and cultural norms characteristics elements implement intopackaging design. Identification of the visual rhetoric elements are important to expresscultural values. New guidance have been introduced to adopting the best visual rhetoricpredominantly cultural expressions on the food packaging design that embrace Malaysiansculture.